Religious values as foundations of education: Insights from teachers’ perspectives - Maksum, Ghufron; Muhtolib; Mahmurudin; Sulaeman; Wiwi Pertiwi; Hidayatul Azizah Gazali; Raudhatul Husna; Zuhrupatul Jannah; Agus Supriadi; Istiqomah; Muzna Attamimi; A. Syaiful Fahmi; et al. (Research Journal in Advanced Humanities, 2025)
The integration of religious values into primary education plays a crucial role in shaping children’s character and morality from an early age. As the forefront of the educational process, teachers hold a strategic role in instilling and exemplifying these values within the school environment. This study aimed to explore primary school teachers’ perspectives on the urgency of embedding religious values in formal education, identify which values are essential to introduce early, and examine the reflective role of teachers as role models and agents of character formation in schools. Adopting a narrative inquiry approach, data were collected through observations, interviews, and documentation. The participants consisted of six primary school teachers with in-depth knowledge of the characteristics of children in their respective teaching contexts. The findings revealed that: (1) religious values should be instilled from an early age as they are fundamental to character building; (2) the values deemed most essential included morality, faith and monotheism, discipline, honesty and justice, politeness and social etiquette, care and responsibility, compassion and empathy, as well as tolerance and cooperation; and (3) teachers served as role models, facilitators, motivators, and mentors who guided and monitored students’ attitudes and behaviors throughout the school day. The implications of this study indicate that integrating religious values into the learning process requires appropriate pedagogical approaches and sustained institutional support. These findings enrich the discourse on religion-based character education at the primary level and pave the way for developing culturally contextualized value-based learning models. Furthermore, the study provides a foundation for future research on the effectiveness of value education interventions across diverse social and cultural contexts.